Development and validation of a practical instrument for evaluating players' familiarity with exergames. Issue 145 (January 2021) - Zhang, Hao; Wang, Di; Wang, Yu; Chi, Ying; Miao, Chunyan
Highlights: An instrument to measure players' perceived familiarity with exergames is presented. The study results suggest good validity and high reliability of the instrument. The instrument can establish players' familiarity level with an exergame. The instrument can contribute to improving the familiarity design of exergames. Abstract: Familiarity design has been widely shown to be beneficial for improving players' perception and adoption of exergames, by reducing their perceived difficulty and complexity. However, players' perceived familiarity with exergames may differ according to their prior knowledge and experience. There still lacks a validated familiarity instrument for measuring players' perceived familiarity with a particular exergame. Such an instrument can inform exergame designers on how well familiarity design has been incorporated into the exergame. Moreover, it helps players to choose an exergame that could induce a higher level of familiarity. In this research, we propose a 10-item psychometric familiarity instrument to evaluate a player's perceived familiarity with exergames. The questions in the instrument are developed based on the sub-constructs of familiarity identified in prior research. To validate the proposed familiarity instrument, we rely on electroencephalogram (EEG) data, which may objectively reflect a player's brain activity when familiarity is induced. A study involving 20 participants indicates that the total scores of the instrument is highly correlated with analyzed results from EEG. The study results suggest good validity and high reliability of our proposed familiarity instrument.